Solute-water interactions in the aquation of Isonicotinohydrazide and nicotinic acid complexes of pentacyanoferrate(n) at various pH - Blesa, Miguel A. (1977)
Fil: Blesa, Miguel A. Comisión Nacional de Energía Atómica; Argentina